ANALYSIS OF CURRENT D'DUKCAPIL INNOVATION PROGRAM PICK UP BETWEEN SERVICES IN VILLAGES AND NEIGHBORHOODS (JALA DI DESAKU) IN BARRU DISTRICT POPULATION AND CIVIL REGISTRATION SERVICES - Kumalasari, Indah (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal